Effect of loading rate and chemical corrosion on the mechanical properties of large diameter glass/basalt-glass FRP bars. (15th September 2015) - Li, Guowei; Wu, Jiantao; Ge, Wanming
Highlights: A novel B-GFRP bar, which is resistant to aggressive environment, was manufactured. The effects of loading rates on tensile mechanical properties of FRP bars were not negligible. The rate-related viscoelastic property of polymer could be dominant in FRP bar tensile test. A new end anchorage system was developed for tensile tests on large diameter FRP bars. Abstract: In this study, the end anchorage device for large diameter FRP bar was firstly developed, based on which the effect of loading rate on the direct tensile mechanical properties of 25 mm diameter GFRP bars was tested, and the anticorrosion properties of a newly developed type of FRP bar, the basalt-glass fiber reinforced polymer (B-GFRP) bars with different thicknesses of basalt FRP protecting layers (0, 1, 3 and 5 mm) were investigated. The results show that, with the increase of loading rate, the tensile strength and elongation ratio of GFRP bar increase considerably, while the elastic modulus remains roughly constant. The addition of BFRP protecting layer is also proved to be an effective way to enhance the resistance of GFRP bars to the chemical attacks.